1996
DOI: 10.1017/s0022215100134176
|View full text |Cite
|
Sign up to set email alerts
|

A cost-benefit analysis of the post-operative use of antibiotic ear drops following grommet insertion

Abstract: A prospective randomized controlled study was carried out to investigate the effect of prophylactic antibiotic ear drops used for five days after bilateral grommet insertion. The average improvement in the hearing threshold was significantly better in ears in which there was an effusion (16 dB) compared with no effusion (9 dB). The drops had no significant effect upon grommet function at three months measured by blockage rates, extrusion rates or improvement in pure tone audiometry whether or not there was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25] Length of tube retention was longer in tubes that manufacturers identified as "long-term tubes." Specifically, Goode T-tubes and Paparella tubes were retained longer than Shah and Shepard tubes.…”
Section: Tympanostomy Tube Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24][25] Length of tube retention was longer in tubes that manufacturers identified as "long-term tubes." Specifically, Goode T-tubes and Paparella tubes were retained longer than Shah and Shepard tubes.…”
Section: Tympanostomy Tube Comparisonsmentioning
confidence: 99%
“…[16][17][18][19][20]22,25,[60][61][62][63] Longer-term tubes related to a higher probability of otorrhea in 3 studies 16,19,60 (low SOE). Evidence about otorrhea was insufficient for other tube comparisons.…”
Section: Tympanostomy Tube Comparisonsmentioning
confidence: 99%
“…Or, by preferentially filling the grommet lumen prevent its immediate blockage with blood. Two studies, one by Salam and Cable, 9 and one by Pearson et al 10 . conclude that antibiotic drops instilled at the time of grommet insertion have no significant effects on blockage rates.…”
Section: Discussionmentioning
confidence: 99%
“…Neither dexamethasone/framecetine nor betamethasone prevented blockage. 45,46 In contrast, a study of high quality 47 showed that obstruction decreased from 15% to 2%-4% by use of floxacillin or neomycin + polymyxin B-hydrocortisone drops.…”
Section: Ventilation Tube Routines For Insertionmentioning
confidence: 97%